Hydrothermally derived porous carbon and its improved electrochemical performance for supercapacitors using redox additive electrolytes. (August 2020) - Kasturi, Palanisamy Rupa; Harivignesh, Ramasamy; Lee, Yun Sung; Selvan, Ramakrishnan Kalai
Abstract: The N-rich porous carbon with high surface area is derived from the starch of Artocarpus heterophyllus seed (AHS) through hydrothermal carbonization (HTC) followed by KOH chemical activation. The EDLC's are fabricated using nitrogen inherited porous carbon with and without the addition of 0.05 M VOSO4 as redox additive in the pristine 0.5 M H2 SO4 electrolyte. The device delivered an ultrahigh specific capacitance of 133 Fg -1 (at a high current of 15 mA) and high specific energy (32 Whkg −1 ) at a specific power of 936 Wkg −1 in the redox electrolyte when compared with pristine 0.5 M H2 SO4 (92 Fg -1 ). Similarly, the symmetric redox-mediated EDLC exhibited extended cyclic stability up to 10, 000 cycles with a coloumbic efficiency of 97%. These outstanding performance of the fabricated EDLC is due to the excellent faradaic interaction between N-rich, surface-functionalized porous carbon electrode with the redox electrolyte at the electrode-electrolyte interface through the redox reaction between VO 2+ /VO2 + species. The present work corroborates that the combination of hydrothermal derived porous carbon (HPAC) and redox additive electrolyte is a promising way to enhance the specific capacitance of the electric double-layer capacitors. Highlights: N-rich sponge-like 3D microporous carbon is prepared through tartaric acid catalysed hydrothermal method. The fabricated EDLC provides high specific energy (32.4 Whkg −1 ) at a specific power of 936.5 Wkg −1 . The surface functionality and VO 2+ /VO 2+ redox reaction at the electrode-electrolyte interface improved the EDLC perfromance.